Value of aspartate aminotransferase/alanine aminotransferase Ratio in predicting coronary thrombus burden in ST elevation myocardial infarction patients undergoing primary percutaneous coronary intervention - Mohamed Aboelhassan; Mohamed A.-K.F. Abdelmegid; Sawsan M. Moeen; Salma M. Hassan; Ishraq H. AbdEl-Hameed; Khaled M.A. Shehata (Al-Azhar Assiut Medical Journal)
Background and aim The liver is extremely responsive to circulatory hemodynamics as a result of its intricate network of blood arteries. Elevated blood transaminase levels are frequently detected in individuals with myocardial infarction, this study is to determine the predictive value of the aspartate aminotransferase/alanine aminotransferase (AST/ALT) ratio and different clinical parameters in assessing the severity of coronary thrombus burden in patients with ST-elevation myocardial infarction (STEMI) undergoing primary PCI. Patients and methods This is a prospective cohort study conducted on 115 patients with acute STEMI (ST segment myocardial infarction) who underwent primary PCI. AST/ALT ratio was calculated for each patient. Evaluation of the extent of thrombus burden using the thrombolysis in myocardial infarction (TIMI) scoring system. Results 56 patients had AST/ALT ratio greater than 2, while 59 patients had AST/ALT ratio less than 2. STEMI patients with AST/ALT ratio greater than 2 had a significantly higher prevalence of total vessel occlusion (TIMI thrombus grade 5), and there is a significant association between high AST/ALT ratio and TIMI thrombus grade 5 on both univariate and multivariate analysis. However, there is no statistically significant difference between both groups as regarding the coronary artery complexity as assessed by SYNTAX and Genseni scores. Conclusion Patients with AST/ALT ratio greater than 2 are strongly associated with high thrombus burden (thrombus burden of 5) on TIMI thrombus grade before primary PCI.